Pengaruh Kemudahan Transaksi dan Layanan Terintegrasi pada Keputusan Penggunaan E-Wallet GoPay : (Survei pada Mahasiswa S1 dan D4 FE UNJ) - Julita Julita; Afya Aulia; Ghina Muthmainnah Zain; Kheisya Nabillah Handayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine whether transaction ease and integrated services influence the decision to use the GoPay e-wallet. The independent variables in this research are transaction ease (X1) and integrated services (X2), while the dependent variable is the decision to use GoPay (Y). The population of this study consists of undergraduate and diploma students (S1 and D4) from the Faculty of Economics at Universitas Negeri Jakarta. The sampling technique employed was random sampling, with primary data collected through a Likert-scale questionnaire. The data obtained were analyzed using Stata 13 software through classical assumption tests and multiple linear regression analysis. The results indicate that, partially, transaction ease and integrated services do not significantly influence the decision to use GoPay. However, simultaneously, these variables collectively affect the decision to use GoPay.